ANALISIS PENDAPATAN DAN PERANAN WANITA DALAM USAHATANI TOMAT LAHAN KERING DI KABUPATEN GRESIK - Ahmad Zubaidi; Astutik Astutik (BUANA SAINS, 2010)
The aim of this research were a) To analysis influence of variable rent farm, price fertilize and labour fee to earnings of dry farming tomato. b) To study storey;level elegibility of dry farming tomato Countryside of Lasem District Of Sidayu Sub-Province of Gresik and c) To Analysis woman labour contribution and role of woman in decision making dry farming tomato. Methodologies used in this study approach qualitative and quantitative by applying case study strategy in this study. Data used in this analysis were with drawal of conclusion presented descriptively, and compilation of program by using method of Focus Group Discussion. Analysis and interprestasi result of research of solution and analysis, can be taken by conclusion that variable rent farm, price fertilize and labour fee by simultan have an effect on to earnings of tomato farming Countryside of Lasem District Of Sidayu Sub-Province of Gresik. And most having an effect on variable/signifikan to earnings of tomato variable rent farm count = 6,649 and value of P = 0,000) and also variable rent farm, price fertilize and labour fee give contribution 74,9% to earnings of farming tomato Countryside of Lasem District Of Sidayu, Sub-Province of Gresik while constribution woman labour activity of production of farming tomato in Countryside of Lasem equal to 54,14% and decision making which concerning tomato farming equal to 42,58